Kekerabatan Antar Anggrek Spesies Berdasarkan Sifat Morfologi tanaman dan Bunga - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Morphological relationships among species orchids is necessay to orchid breeder in obtaining good hybrids in perennial plants. Closely related among species orchids would increase their crossing opportunity. The objectives of this study was to classify orchid into cluster according to their similarities in phenotypic characters. The phenotypic characters observed were plant height (cm), leaf length (cm), leaf width (cm), ratio of leaf length and leaf width number of flowers per inflorescence, lenght offlower stalk (cm), flower diameter (cm), sepala lenght (cm), leaf colon